Turkish Shakespeare Studies: An Origins Story - Öğütcü, Murat (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
Shakespeare is among the most important non-Turkish authors in Turkey and has become an indispensable part of the theatre repertory and the educational curricula. Yet, the origins of Shakespeare studies have a complicated legacy dating back to the imperialistic motivations of foreign schools in Ottoman Turkey. However, starting with the republican period, Shakespeare productions and studies were utilised to spread the progressive reforms of the republic that were maintained through the theatres and the various universities primarily set in Istanbul and in Ankara. Accordingly, this article will explore the origins of the academic study of Shakespeare in Turkey.